Comparison of digital assessment and documentation systems used in the early childhood education in Turkey, Germany and Spain - Özdil, Gülşah; Simsek, Fatma Merve; Tuğluk, Mehmet Nur (Southeast Asia Early Childhood Journal, 2021)
This is a comparative education study that aims to compare the digital documentation systems used in the preschool education programs and institutions in Turkey, Germany and Spain and to reveal the similarities and differences between these systems. The study was planned as a qualitative research in terms of its descriptive aspect, and as a comparative educational study in terms of its content and method. Comparative education helps us to understand how education systems are shaped by the wealth, ideology, social-cultural characteristics of the country, and the effects of globalization on educational policies and practices in different regions and countries. The study aims to examine the existing data through document analysis and to compare and better understand preschool education conditions by making in-depth observations in order to compare digital documentation systems by focusing on the dimension of observation. The study group consists of the digital documentation systems used in Turkey, Germany and Spain. The EBA system developed by the Ministry of Education in Turkey, KITALINO digital documentation used in Germany and Transparent Classroom application used in Spain were examined in the study. In the analysis of the data, digital documentation systems were shown in tables in line with the determined criteria and comparisons were made. Based on these comparisons, comments and suggestions were made. It was observed in accordance with the results of the comparative education study that there are various applications in the early childhood education in Turkey, Germany and Spain in terms of digital documentation.